Aging Population and Public Pensions: Theory and Macroeconometric Evidence - Verbič, Miroslav; Spruk, Rok (Panoeconomicus, 2014)
Rapidly aging population in high-income countries has exerted additional pressure on the sustainability of public pension expenditure. We present a theoretical model of public pension expenditure under endogenous human capital, where the latter facilitates a substantial decrease in equilibrium fertility rate alongside the improvement in life expectancy. We demonstrate how higher life expectancy and human capital endowment facilitate a rise of net replacement rate. We then provide and examine an empirical model of old-age expenditure in a panel of 33 countries for the period 1998-2008. Our results indicate that increases in effective retirement age and total fertility rate would reduce age-related expenditure substantially. While higher net replacement rate would alleviate the risk of old-age poverty, further increases would add considerable pressure on the fiscal sustainability of public pensions. Key words: Public pensions, Ageing, Social security, Replacement rate, Life expectancy. JEL: H55, J11, C54.